Banyuwangi Gandrung Dance as a Source of Ideas for Creating Evening Wear with Embroidered Gajah Oling Motifs and Sequence - Dafira``, Rana Alya; Arifiana, Deny; Nahari, Inty; Kharnolis, Mein (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Gandrung Dance is an art form dominated by dance with a typical orchestra popular in the Banyuwangi area. Gandrung dance has also become a dance for welcoming guests at various arts events as well as state events, so it is not wrong that Banyuwangi is often nicknamed the City of Gandrung. Evening wear is evening party clothing using high quality materials complete with decorative accessories to make the clothing look luxurious. Based on wanting to introduce more about Gandrung dance ornaments and clothing which have high cultural and artistic value through the stylization process into evening dresses that can depict the beauty of Gandrung dance in the form of evening wear. The aim of this research is to describe the process and results of creating evening wear designs using embroidered gajah oling motifs and sequins using the idea of the Gandrung Banyuwangi dance. This research includes creation or development research, which uses the Practice-Ied Research method, which consists of 4 stages, including: (1) Pre-design, (2) Design, (3) Realization, (4) Presentation. The results of this research show that: (1) the process of creating evening wear designs using the idea of the Gandrung Banyuwangi dance as a source (2) The results of the creation are 3 evening wear consisting of 2 female evening wear designs and 1 male evening wear design, for women there are 2 looks where the look 1 there are 3 pieces consisting of a span skirt, draped skirt, bustier, capuchon shawl, the 2nd look consists of a bustier and a puffed skirt, the male fashion look is a vest and trousers.